Effect of oregano essential oil on intestinal immunoglobulin G in Holstein dairy bulls - Xu, Meiling; Zhang, Wangdong; Kong, Fanyun; Wang, Baoshan; Pan, Jing; Shi, Jinping; Liu, Qiyan; He, Pengjia; Ma, Yue; Cheng, Qiang; Zhang, Zhao; Lei, Zhaomin (Frontiers in Veterinary Science, 2024)
Introduction Immunoglobulin G (IgG) is important in mediating humoral immunity and in the maintenance of immune homeostasis in the intestinal mucosa. Oregano essential oil (OEO) is a natural herbal extract that possesses antimicrobial, antioxidant, anti-inflammatory, and immunomodulatory properties. As the effects of OEO on intestinal mucosal immunity in Holstein dairy bulls remained unclear, we investigated the effect of dietary supplementation of OEO on IgG levels and IgG+ cells residing in the intestinal tract in Holstein dairy bulls. Methods Twelve Holstein bulls in good health of approximately 10 months of age were selected for the experiment and randomly equally divided into two groups. The control (CK) group was fed a basal ration, and in the OEO group, the basal ration was supplemented with OEO (20 g/head/day). After 300 days of feeding, tissue samples of the jejunum, ileum, and colon of the bulls in each group were collected for histopathological analysis, immunohistochemistry, and enzyme-linked immunosorbent assays, respectively. Results The jejunum, ileum, and colon of bulls in the CK group had obvious pathological damage, whereas the structure of each intestinal segment was clear and intact. In the OEO group, pathological damage was significantly reduced. IgG+ plasma cells were diffusely distributed in the lamina propria of the jejunum, ileum, and colon in the CK and OEO groups, with no significant difference between the groups. OEO supplementation significantly reduced the number of IgG+ plasma cells in each intestinal segment, with the highest decrease rate being noted for the ileum (22.87%), followed by the colon (19.45%) and jejunum (8.52%). ELISA test results and immunohistochemical results were mutually verified. The change in IgG content was consistent with the trend of change in the number of IgG+ plasma cells. Discussion Our findings suggest that OEO supplementation does not alter the diffuse spatial distribution of IgG+ plasma cells in the intestines of Holstein dairy bulls, but lowers immunoglobulin levels to normal levels, significantly reduces intestinal damage, and may enhance mucosal immune defence barrier function by inhibiting inflammatory reactions.